2023
DOI: 10.1007/s10646-023-02706-y
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data

Christopher J. Sayers,
David C. Evers,
Viviana Ruiz-Gutierrez
et al.

Abstract: Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…Many species of invertebrate-eating birds (herein called landbirds) are also at elevated risk to Hg exposure. Remarkably, landbirds can exhibit higher tissue Hg concentrations than fish-eating birds within the same ecosystem (Evers et al 2005 ; Kopec et al 2018 ; Sayers et al 2023 ). They may also be more sensitive to MeHg, resulting in a higher likelihood of adverse impacts on reproductive success (Heinz et al 2009 ; Jackson et al 2011b ; Whitney and Cristol 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of invertebrate-eating birds (herein called landbirds) are also at elevated risk to Hg exposure. Remarkably, landbirds can exhibit higher tissue Hg concentrations than fish-eating birds within the same ecosystem (Evers et al 2005 ; Kopec et al 2018 ; Sayers et al 2023 ). They may also be more sensitive to MeHg, resulting in a higher likelihood of adverse impacts on reproductive success (Heinz et al 2009 ; Jackson et al 2011b ; Whitney and Cristol 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“… Note that bioindicators for human exposure are also useful for environmental assessments 1 Kenney et al ( 2014 ), 2 AMAP 2011 ), 3 Rigét et al ( 2007 ), 4 Evers et al ( 2014 ), 5 Jackson et al ( 2016 ), 6 Braune 2007 ), 7 Routti et al ( 2011 ), 8 Dietz et al ( 2013 ), 9 Gantner et al ( 2010 ), 10 Eagles-Smith et al ( 2016a ), 11 Sayers et al ( 2023 ), 12 Wagemann and Kozlowska ( 2005 ), 13 Wiener et al ( 2012a ), 14 Weis and Khan ( 1990 ), 15 Evers et al ( 2011b ), 16 Bowerman et al ( 1994 ), 17 Odsjö et al ( 2004 ), 18 Jackson et al ( 2015 ), 19 Wiemeyer et al ( 1988 ), 20 Goodale et al ( 2008 ), 21 Yates et al ( 2005 ), 22 Klenavic et al ( 2008 ), 23 Brookens et al ( 2008 ), 24 Dam and Bloch ( 2000 ), 25 Eagles-Smith and Ackerman ( 2009 ), 26 Ackerman et al ( 2016 ), 27 Frederick et al ( 2002 ), 28 Braune ( 1987 ), 29 Day et al ( 2005 ), 30 Kamman et al ( 2005 ), 31 Monson et al ( 2011 ), 32 Cai et al ( 2007 ), 33 Bastos et al ( 2015 ), 34 Mol et al ( 2001 ), 35 Lane et al ( 2011 ), 36 Townsend et al ( 2013 ), 37 Finkelstein et al ( 2006 ), 38 Burger and Gochfeld ( …”
Section: Methodsmentioning
confidence: 99%
“…In an analysis from Madre de Dios that included birds of all trophic guilds, feather samples from mining-impacted sites contained 6.7 times higher Hg [95]. The samples from ASGM-impacted areas were also the highest in the published literature to date [94,95].…”
Section: Dietary Hg Exposure Risk From Chicken Consumptionmentioning
confidence: 98%
“…Nevertheless, it is well-established that ASGM is a major driver of Hg accumulation in numerous avian species. In an analysis of mercury concentrations in neotropical birds across Central and South America, Sayers et al [94] noted that birds within 7 km of mining activity exhibited four times higher Hg concentrations than other sites. In an analysis from Madre de Dios that included birds of all trophic guilds, feather samples from mining-impacted sites contained 6.7 times higher Hg [95].…”
Section: Dietary Hg Exposure Risk From Chicken Consumptionmentioning
confidence: 99%
“…The rate of Hg biomagnification in ecosystems is linked to the latitude of these ecosystems, physico-chemical parameters, and the pool of Hg present in the ecosystem [ 12 ]. In general, tropical ecosystems have lower biomagnification factors than temperate ecosystems [ 12 ], however, several studies have showed that Hg concentrations in top predators in tropical regions are high [ [13] , [14] , [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%